Glass fiber reinforced nylon composite material as well as preparation method and application thereof

Through the composite technology of modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant, glass fiber reinforced nylon composite materials were prepared, solving the problem of reduced flame retardant performance of nylon materials when improving surface resistance, achieving efficient and economical permanent anti-static and flame retardant performance, and is suitable for a variety of industrial applications.

CN119529525APending Publication Date: 2025-02-28SUZHOU HEGENGLI PLASTIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411860914.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

While improving the surface resistance of nylon materials, the prior art will lead to a reduced flame retardant performance, and the preparation process is complicated, making it difficult to directly purchase the additives used, resulting in high costs.

Method used

Modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant were used for composite preparation to prepare glass fiber reinforced nylon composite material, combined with nylon resin and glass fiber, and prepared through a twin-screw extruder.

Benefits of technology

It achieves the maintenance of good mechanical properties, and has both permanent antistatic properties and good flame retardant properties (V-0 level), and the preparation process is simple, low cost, and meets the requirements of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193180040000071
    Figure BDA0005193180040000071
  • Figure BDA0005193180040000101
    Figure BDA0005193180040000101
  • Figure BDA0005193180040000111
    Figure BDA0005193180040000111
Patent Text Reader

Abstract

The invention relates to a glass fiber reinforced nylon composite material as well as a preparation method and application thereof. The glass fiber reinforced nylon composite material is prepared from the following raw materials: nylon resin, modified carbon nanotubes, a halogen-free flame retardant and a red phosphorus flame retardant, the halogen-free flame retardant comprises an organic phosphate halogen-free flame retardant and / or a P-N halogen-free flame retardant. The glass fiber reinforced nylon composite material provided by the invention has good flame retardant property and excellent permanent antistatic property while having relatively good mechanical property; meanwhile, the preparation process is simple, convenient to operate, low in raw material cost, halogen-free, economical and safe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a glass fiber reinforced nylon composite material and a preparation method and application thereof. Background Art

[0002] Nylon (Polyamide, PA) is one of the five major engineering plastics, with excellent mechanical properties, heat resistance, self-lubricating properties and other properties. Due to the presence of amide groups in the molecular chain, nylon has a certain degree of flame retardancy, which can reach the V-2 level in the UL-94 standard. It needs to add additional flame retardants to reach the V-0 level to meet the needs of the electronics and electrical industries. Commonly used flame retardants are halogenated flame retardants and halogen-free flame retardants mainly based on bromine. Today, when the concept of green environmental protection is deeply rooted in people's hearts, halogen-free flame retardants are becoming more and more popular.

[0003] In some special fields such as materials used in mines, flame retardant nylon has antistatic requirements. As an electrical insulating polymer, nylon has a surface resistance of 10 14-16 Ω, and the surface resistance reaches 10 8-10 The presence of amide bonds makes nylon extremely absorbent, and after long-term storage, the surface resistance will decrease and even reach the antistatic level, but this antistatic property is difficult to control artificially.

[0004] Antistatic nylon includes short-term antistatic and permanent antistatic. The principle of short-term antistatic agent is to add surfactants that can easily migrate to the surface of the material so that it can quickly absorb water on the surface of nylon to form a water film to play an antistatic role. The disadvantage is that the antistatic agent loses its effectiveness after migration. Permanent antistatic is to form a conductive circuit inside the material, generally adding materials such as carbon fiber, conductive carbon black, and carbon nanotubes.

[0005] The research on flame-retardant and antistatic nylon has gradually become a hot topic. CN115948049B adds conductive carbon materials to prepare halogen-free flame-retardant and antistatic nylon; CN110511562B adds basic magnesium chloride as a flame retardant, and uses the water-absorbing property of the material to form a water film on the surface of the material to reduce the surface resistance of nylon; CN114806155B adds surfactant sodium polystyrene sulfonate to achieve antistatic effect. However, the above patents focus on improving the surface resistance of the material, and the negative impact on the flame retardant properties of the material has not been resolved. In addition, the preparation process of the above patents is complicated, and the additives used cannot be purchased directly on the market.

[0006] Therefore, in view of the technical defects in the prior art that while improving the surface resistance of nylon materials will reduce their flame retardant properties, how to design and develop a permanent antistatic halogen-free flame retardant glass fiber reinforced nylon material that takes into account antistatic properties, flame retardant properties, and mechanical properties without significantly increasing costs has become a problem that needs to be solved urgently. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a glass fiber reinforced nylon composite material and its preparation method and application. The glass fiber reinforced nylon composite material has permanent antistatic properties and good flame retardant properties while maintaining good mechanical properties, and has a simple preparation process, low production cost, and is green and safe.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a glass fiber reinforced nylon composite material, wherein raw materials for preparing the glass fiber reinforced nylon composite material include nylon resin, modified carbon nanotubes, a halogen-free flame retardant and a red phosphorus flame retardant.

[0010] The halogen-free flame retardant includes an organic phosphate halogen-free flame retardant and / or a PN halogen-free flame retardant.

[0011] In the present invention, modified carbon nanotubes, halogen-free flame retardants and red phosphorus flame retardants are specifically selected for compounding, and the halogen-free flame retardants include organic phosphate halogen-free flame retardants and / or PN halogen-free flame retardants, so that the obtained glass fiber reinforced nylon composite material has good mechanical properties, flame retardant properties and permanent antistatic properties, and at the same time does not significantly increase the cost, is green and economical, and has high practical value.

[0012] In actual production, when carbon nanotubes are added to a glass fiber reinforced nylon material system containing only halogen-free flame retardants (organophosphate halogen-free flame retardants and / or PN halogen-free flame retardants), the flame retardant effect is poor; when they are added to a glass fiber reinforced nylon material system containing only red phosphorus flame retardants, the flame retardant performance is minimally affected, but the already low mechanical properties will be further reduced, resulting in poor overall technical effects of the resulting composite material. For the conductive carbon fiber in the prior art, when it is used, although the combination with the PN halogen-free flame retardant does not affect the flame retardant effect, when the amount added is small, its technical effect is not as good as that of carbon nanotubes of the same mass. Only when it is added to 8-10 parts by weight can a stable conductive circuit be formed, and at this time the resistance is reduced to 10 5 -10 6Ω, and because carbon fiber is expensive, the cost of raw materials will be too high, which is not conducive to the improvement of industrial production efficiency; in addition, carbon fiber has a larger aspect ratio, and compared with carbon nanotubes, it is not easy to disperse and has more serious orientation, which has a greater impact on the conductive stability at low addition content. As for the conductive agent conductive carbon black, although the price is cheap, the resistance of the composite material prepared therefrom is unstable, and it is easy to precipitate and fall off, which is not conducive to actual production application. Compared with ionic antistatic agents, the carbon nanotubes of the present invention have better antistatic effects. Therefore, in the present invention, the specific carbon nanotubes are selected to be compounded with halogen-free flame retardants and red phosphorus flame retardants, which has the dual advantages of low cost and high performance.

[0013] In the present invention, the halogen-free flame retardant includes an organic phosphate halogen-free flame retardant and / or a PN halogen-free flame retardant. Since the PN halogen-free flame retardant has a more cost-effective advantage, the halogen-free flame retardant in the present invention is further preferably the PN halogen-free flame retardant.

[0014] Preferably, the nylon resin includes any one of PA6, PA66, PA6I, PA612, PPA or PA46, or a combination of at least two of them, for example, a combination of PA6 and PA66, a combination of PA66 and PA6I, a combination of PA612 and PA6, a combination of PA66 and PA46, or a combination of PA6, PA66 and PA6I, a combination of PA6I, PPA and PA66, etc.

[0015] Preferably, the content of nylon resin in the preparation raw material is 49-60 parts by weight, for example, it can be 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight or 59 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0016] Preferably, the modified carbon nanotubes are obtained by pre-treating carbon nanotubes.

[0017] Preferably, the pretreatment comprises mixing the carbon nanotubes with a modifying agent.

[0018] Preferably, the carbon nanotubes include agglomerated multi-walled carbon nanotubes and arrayed multi-walled carbon nanotubes.

[0019] Preferably, the modifying agent comprises silicone oil.

[0020] The carbon nanotubes provided by the present invention are array-type multi-walled carbon tubes with a flaky appearance. They are easily dispersed in silicone oil, which not only effectively avoids their own agglomeration, but also helps to evenly distribute them in nylon resin, thereby helping to improve the obtained glass fiber reinforced nylon composite material to obtain stable and efficient permanent antistatic performance.

[0021] Preferably, the silicone oil includes any one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil or hydrogen-containing silicone oil, or a combination of at least two thereof.

[0022] Preferably, the mass ratio of the carbon nanotubes to the modifying agent is 1:(0.8-1.5), wherein the specific value of (0.8-1.5) can be, for example, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.2, 1.3, 1.4 or 1.45, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0023] Preferably, the mixing is performed under stirring.

[0024] Preferably, the stirring speed is 60-100 r / min, for example, it can be 60 r / min, 70 r / min, 80 r / min, 90 r / min or 100 r / min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0025] Preferably, the stirring time is 2-3 min, for example, 2 min, 2.5 min or 3 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0026] In the present invention, the stirring speed and time of the pretreatment are controlled within a specific range. If the speed is lower than the range, the mixing effect is poor. If the speed is higher than the range, a centrifugal effect may be generated during the stirring process, causing the carbon nanotubes to float on the edge of the barrel and the surface of the mixture, resulting in poor dispersion effect, thereby affecting the antistatic stability of the obtained glass fiber reinforced nylon composite material.

[0027] Exemplarily, the method for pretreating carbon nanotubes in the present invention comprises the following steps:

[0028] The carbon nanotubes and the modification agent in a mass ratio of 1:(0.8-1.5) are stirred at 60-100 r / min for 2-3 minutes to obtain the modified carbon nanotubes.

[0029] In the present invention, the modified carbon nanotubes are obtained by pre-treating the carbon nanotubes, so that the carbon nanotubes are dispersed more evenly in the nylon resin, and are more likely to form a stable conductive circuit, thereby facilitating the obtaining of a glass fiber reinforced nylon composite material with stable permanent antistatic properties. However, the carbon nanotubes that are not pre-treated will agglomerate more seriously in the twin-screw extruder, and will be dispersed unevenly, and in severe cases, will not even be well combined with the nylon resin, thereby making the resistance of the glass fiber reinforced nylon composite material unstable, and thus failing to exert a good antistatic effect.

[0030] Preferably, the content of modified carbon nanotubes in the preparation raw material is 1.5-4 parts by weight, for example, it can be 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight or 4 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0031] Preferably, the content of the halogen-free flame retardant in the preparation raw material is 4-12 parts by weight, for example, it can be 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight or 12 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0032] Preferably, the content of red phosphorus flame retardant in the preparation raw material is 3-10 parts by weight, for example, it can be 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0033] Preferably, the mass ratio of the halogen-free flame retardant to the red phosphorus flame retardant is (5:9)-(10:4), for example, it can be 5:9, 6:8, 7:7, 8:6, 9:5 or 10:4, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0034] In the present invention, when the mass ratio of the halogen-free flame retardant to the red phosphorus flame retardant is within a specific range, the compounding thereof with the modified carbon nanotubes can exert a good synergistic effect, so that the obtained glass fiber reinforced nylon composite material obtains a better comprehensive effect in terms of mechanical properties, flame retardant properties and antistatic properties. When the mass ratio of the halogen-free flame retardant to the red phosphorus flame retardant is lower than 5:9, the mechanical properties are greatly attenuated and the improvement of the flame retardancy is not obvious; when the mass ratio of the two is higher than 10:4, although the mechanical properties will be slightly improved, the 1.5mm thickness V-0 grade flame retardant cannot be guaranteed to be stable.

[0035] Preferably, the organic phosphate halogen-free flame retardant includes diethyl hypophosphite halogen-free flame retardant.

[0036] Preferably, the diethyl phosphite halogen-free flame retardant includes diethyl zinc phosphite and / or diethyl aluminum phosphite.

[0037] Preferably, the raw materials for preparing the glass fiber reinforced nylon composite material also include glass fiber and lubricant.

[0038] Preferably, the length of the glass fiber is 3.0-4.5 mm, for example, it can be 3.2 mm, 3.4 mm, 3.6 mm, 3.8 mm, 4.0 mm, 4.2 mm or 4.4 mm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0039] Preferably, the diameter of the glass fiber is 9-11 μm, for example, it can be 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm, 10 μm, 10.2 μm, 10.4 μm, 10.6 μm, 10.8 μm or 11 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0040] Preferably, the content of glass fiber in the preparation raw material is 25-35 parts by weight, for example, it can be 26 parts by weight, 27 parts by weight, 28 parts by weight, 29 parts by weight, 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight or 34 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0041] Preferably, the lubricant includes any one of N,N′-bis(ethylene) stearic acid amide, stearic acid amide, paraffin wax, polyethylene wax, polypropylene wax or silicone, or a combination of at least two of them.

[0042] Preferably, the content of lubricant in the preparation raw material is 0.1-0.5 weight part, for example, it can be 0.15 weight part, 0.2 weight part, 0.25 weight part, 0.3 weight part, 0.35 weight part, 0.4 weight part or 0.45 weight part, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] Preferably, the raw materials for preparing the glass fiber reinforced nylon composite material include the following components in parts by weight:

[0044]

[0045] In a second aspect, the present invention provides a method for preparing the glass fiber reinforced nylon composite material as described in the first aspect, the preparation method comprising the following steps:

[0046] Components including nylon resin, modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant are mixed, melt-extruded and granulated to obtain the glass fiber reinforced nylon composite material.

[0047] Preferably, the mixing rotation speed is 80-120 r / min, for example, it can be 80 r / min, 90 r / min, 100 r / min, 110 r / min or 120 r / min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0048] Preferably, the mixing time is 6-8 min, for example, 6 min, 6.5 min, 7 min, 7.5 min or 8 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] Preferably, the melt extrusion is carried out in a twin-screw extruder.

[0050] Preferably, the temperature of each section of the twin-screw extruder is set as follows: the temperature of zone 1 is 260-280°C (for example, it can be 260°C, 265°C, 270°C, 275°C or 280°C, etc.), the temperature of zone 2 is 280-300°C (for example, it can be 280°C, 285°C, 290°C, 285°C or 300°C, etc.), the temperature of zone 3 is 280-300°C (for example, it can be 280°C, 285°C, 290°C, 295°C or 300°C, etc.), the temperature of zone 4 is 280-300°C (for example, it can be 280°C, 285°C, 290°C, 295°C or 300°C, etc.), the temperature of zone 5 is 280-300°C (for example, it can be 280°C, 285°C, 290°C, 295°C or 300°C, etc. Or 300℃, etc.), the temperature of zone six is ​​240-260℃ (for example, it can be 240℃, 245℃, 250℃, 255℃ or 260℃, etc.), the temperature of zone seven is 200-220℃ (for example, it can be 200℃, 205℃, 210℃, 215℃ or 220℃, etc.), the temperature of zone eight is 190-210℃ (for example, it can be 190℃, 195℃, 200℃, 205℃ or 210℃, etc.), the temperature of zone nine is 180-200℃ (for example, it can be 180℃, 185℃, 190℃, 195℃ or 200℃, etc.), and the temperature of the die is 260-270℃ (for example, it can be 260℃, 262℃, 264℃, 266℃, 268℃ or 270℃, etc.).

[0051] Preferably, the residence time in the twin-screw machine is 1-2 min, for example, it can be 1.2 min, 1.4 min, 1.6 min, 1.8 min or 2 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Preferably, the pressure in the twin-screw extruder is 10-16 MPa, for example, it can be 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa or 16 MPa, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0053] Exemplarily, the preparation method of the glass fiber reinforced nylon composite material provided by the present invention specifically comprises the following steps:

[0054] (1) mixing nylon resin, halogen-free flame retardant, red phosphorus flame retardant, lubricant and modified carbon nanotubes at a rotation speed of 80-120 r / min for 6-8 min;

[0055] (2) The raw materials mixed uniformly in step (1) are put into a twin-screw extruder, and glass fiber is added to the side feed for pelletizing. The temperature of each section of the twin-screw extruder is set as follows: the temperature of zone 1 is 260-280°C, the temperature of zone 2 is 280-300°C, the temperature of zone 3 is 280-300°C, the temperature of zone 4 is 280-300°C, the temperature of zone 5 is 280-300°C, the temperature of zone 6 is 240-260°C, the temperature of zone 7 is 200-220°C, the temperature of zone 8 is 190-210°C, the temperature of zone 9 is 180-200°C, and the head temperature is 260-270°C; the residence time in the twin-screw machine is 1-2 minutes, and the pressure is 10-16MPa.

[0056] In a third aspect, the present invention provides an application of the glass fiber reinforced nylon composite material as described in the first aspect in the mining industry, the automotive industry, and the electronic and electrical fields.

[0057] Compared with the prior art, the present invention has at least the following beneficial effects:

[0058] The present invention adds modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant components into the system of nylon resin and glass fiber to obtain a permanent antistatic halogen-free flame retardant glass fiber reinforced nylon composite material, which can have good mechanical properties, good flame retardant properties (V-0) and excellent permanent antistatic properties (surface resistance can reach 10 9 Ω); further, the preparation process of the glass fiber reinforced nylon composite material provided by the present invention is simple, easy to operate, has low raw material cost, does not contain halogen, and is economical and safe. DETAILED DESCRIPTION

[0059] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0060] The raw materials used in the following examples are all commercially available, and some of the raw material information is as follows:

[0061] Silicone oil: polydimethylsiloxane, MK 012 / -3 / -4 / -5, Shenzhen Daxing Chemical Co., Ltd.;

[0062] Diethyl hypophosphite halogen-free flame retardant: OP1230, Clariant;

[0063] PN halogen-free flame retardant: 5204GM, Guangdong Shunde Tongcheng New Materials;

[0064] Red phosphorus flame retardant: 9950T, Tongcheng Xinde New Materials;

[0065] Carbon nanotubes: BT1001M, LG Chem;

[0066] Antistatic agent: HS-1, Clariant;

[0067] PA66: EP158, Huafeng;

[0068] PA66: HY1500, Jiangsu Huayang Nylon;

[0069] PA6: C500 / 275, Zhejiang Hengyi;

[0070] PA6I: A1315, Beijing Anaiji;

[0071] Lubricant: Siloxane PA44520, Wacker Chemicals;

[0072] Glass fiber: ECS301HP-3-H, Chongqing International Composite Materials Co., Ltd.

[0073] Example 1

[0074] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:

[0075]

[0076] Carbon nanotube pretreatment method:

[0077] The carbon nanotubes and polydimethylsiloxane in a mass ratio of 1:1 were stirred at 60 r / min for 3 min to obtain the modified carbon nanotubes.

[0078] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:

[0079] (1) EP158, HY1500, 5204GM, 9950T, lubricant and modified carbon nanotubes were mixed at a rotation speed of 100 r / min for 6 min;

[0080] (2) The raw materials mixed evenly in step (1) are put into a twin-screw extruder, and glass fiber is added to the side feed for pelletizing. The temperature of each section of the twin-screw extruder is set as follows: the temperature of zone 1 is 270°C, the temperature of zone 2 is 290°C, the temperature of zone 3 is 290°C, the temperature of zone 4 is 290°C, the temperature of zone 5 is 290°C, the temperature of zone 6 is 250°C, the temperature of zone 7 is 210°C, the temperature of zone 8 is 200°C, the temperature of zone 9 is 190°C, and the head temperature is 265°C; the residence time in the twin-screw machine is 2 minutes, and the pressure is 13 MPa.

[0081] Example 2

[0082] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:

[0083]

[0084] Carbon nanotube pretreatment method:

[0085] The carbon nanotubes and polydimethylsiloxane in a mass ratio of 1:1.5 were stirred at 100 r / min for 2 minutes to obtain the modified carbon nanotubes.

[0086] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:

[0087] (1) C500 / 275, 5204GM, 9950T, lubricant and modified carbon nanotubes were mixed at a rotation speed of 120 r / min for 6 min;

[0088] (2) The raw materials mixed uniformly in step (1) are put into a twin-screw extruder, and glass fiber is added to the side feed for pelletizing. The temperature of each section of the twin-screw extruder is set as follows: the temperature of zone 1 is 260°C, the temperature of zone 2 is 280°C, the temperature of zone 3 is 280°C, the temperature of zone 4 is 280°C, the temperature of zone 5 is 280°C, the temperature of zone 6 is 240°C, the temperature of zone 7 is 200°C, the temperature of zone 8 is 190°C, the temperature of zone 9 is 180°C, and the head temperature is 260°C; the residence time in the twin-screw machine is 1.5 min, and the pressure is 16 MPa.

[0089] Example 3

[0090] This embodiment provides a glass fiber reinforced nylon composite material, the raw materials for preparing the composite material include the following components in parts by weight:

[0091]

[0092] Carbon nanotube pretreatment method:

[0093] The carbon nanotubes and polydimethylsiloxane in a mass ratio of 1:0.8 were stirred at 80 r / min for 2.5 min to obtain the modified carbon nanotubes.

[0094] The preparation method of the glass fiber reinforced nylon composite material comprises the following steps:

[0095] (1) EP158, A1315, OP1230, 9950T, lubricant and modified carbon nanotubes were mixed at a rotation speed of 80 r / min for 8 min;

[0096] (2) The raw materials mixed evenly in step (1) are put into a twin-screw extruder, and glass fiber is added to the side feed for pelletizing. The temperature of each section of the twin-screw extruder is set as follows: the temperature of zone 1 is 280°C, the temperature of zone 2 is 300°C, the temperature of zone 3 is 300°C, the temperature of zone 4 is 300°C, the temperature of zone 5 is 300°C, the temperature of zone 6 is 260°C, the temperature of zone 7 is 220°C, the temperature of zone 8 is 200°C, the temperature of zone 9 is 190°C, and the head temperature is 270°C; the residence time in the twin-screw machine is 1 min, and the pressure is 10 MPa.

[0097] Comparative Example 1

[0098] This comparative example provides a glass fiber reinforced nylon composite material, which is different from Example 1 only in that modified carbon nanotubes are not added, and other raw materials, contents and preparation methods are the same as those in Example 1.

[0099] Comparative Example 2

[0100] This comparative example provides a glass fiber reinforced nylon composite material, which differs from Example 1 in that 3 parts by weight of modified carbon nanotubes are replaced by 3 parts by weight of carbon nanotubes, and other raw materials, contents and preparation methods are the same as those in Example 1.

[0101] The preparation methods of Examples 4-9 and Comparative Examples 3-5 are the same as that of Example 1, and the weight proportions of the corresponding raw material components are shown in Table 1.

[0102] Table 1

[0103]

[0104] The above-mentioned Examples 1-9 and Comparative Examples 1-5 were subjected to performance tests, and the test standards are shown in Table 2.

[0105] Table 2

[0106]

[0107]

[0108] The test results are shown in Table 3.

[0109] Table 3

[0110]

[0111] The test results show that:

[0112] (1) It can be seen from Examples 1-3 that the present invention, by adding components such as modified carbon nanotubes, halogen-free flame retardants and red phosphorus flame retardants to the system of nylon resin and glass fiber, ensures that the obtained glass fiber reinforced nylon composite material has good mechanical properties while also having good flame retardant properties (1.5mm V-0) and excellent permanent antistatic properties.

[0113] (2) By comparing Example 1 with Example 4, it can be seen that compared with the expanded PN composite flame retardant, when the halogen-free flame retardant selects organic phosphate, it is compounded with the red phosphorus flame retardant and the modified carbon nanotubes, which can make the glass fiber reinforced nylon composite material have excellent flame retardant properties and permanent antistatic properties, while its mechanical properties are better, but it will cause an increase in cost.

[0114] (3) It can be seen from Examples 1 and 5-9 that the mass ratio of the halogen-free flame retardant to the red phosphorus flame retardant in Example 7 is 4:10, which is lower than the specific mass ratio range of the two (5:9)-(10:4). At this time, the content of the halogen-free flame retardant is low, and its 1.5mm V-0 flame retardant can stably pass, and the resistance is stable at 10 9 Ω, but the mechanical properties, especially the impact strength, are greatly reduced compared with those in Example 1; in Example 8, the mass ratio of the halogen-free flame retardant to the red phosphorus flame retardant is 11:3, which is higher than the specific mass ratio range of the two (5:9)-(10:4). At this time, the content of the halogen-free flame retardant is high, the mechanical properties are good and the resistance is stable, but the flame retardant performance is greatly reduced, and both 1.5mm and 3.0mm can only reach the V-1 level; further, by comparing Example 8 with Example 9, it can be seen that as the content of the halogen-free flame retardant increases, the mechanical properties show a downward trend and the surface resistance remains stable at 10 9 Ω, the flame retardant performance is improved to a certain extent, but 1.5mm can only reach V-1, and unnecessary cost investment is also increased. Therefore, it is shown that the present invention further optimizes the mass ratio of PN halogen-free flame retardant and red phosphorus flame retardant, so that when the mass ratio of the two is (5:9)-(10:4), the obtained glass fiber reinforced nylon composite material can have excellent flame retardancy and permanent antistatic properties while ensuring good mechanical properties, and the raw material cost is low, economical and safe.

[0115] (4) By comparing Example 1 with Comparative Example 1, it can be seen that the glass fiber reinforced nylon composite material obtained in Comparative Example 1 has excellent flame retardant and mechanical properties, especially impact strength, which is much higher than that of the composite material with modified carbon nanotubes added, but its surface resistance reaches 10 14 Ω, does not have excellent antistatic properties.

[0116] (5) By comparing Example 1 with Comparative Example 2, it can be seen that if the modified carbon nanotubes in the present invention are replaced with carbon nanotubes that have not been pretreated, the flame retardant properties of the obtained glass fiber reinforced nylon composite material do not change significantly, but the surface resistance is extremely unstable. When the effective component of the conductive additive (carbon nanotubes) is doubled, the resistance is still within 10 8 Ω to 10 11 This is because the uneven dispersion of carbon nanotubes leads to agglomeration during the processing and no good circuit is formed, so that the surface resistance is unstable, which further shows that the addition of modified carbon nanotubes in the present invention can effectively improve the permanent antistatic properties of glass fiber reinforced nylon composite materials.

[0117] (6) By comparing Example 1 with Comparative Examples 3-5, it can be seen that when the content of other components added remains unchanged, the flame retardant system in Comparative Example 3 contains only PN type flame retardant, and its flame retardant performance is greatly affected, and can only reach V-2 at 3.0 mm; the flame retardant system in Comparative Example 4 contains only red phosphorus flame retardant, and its flame retardant performance is good and can reach 1.5 mm V-0, but the mechanical properties are much lower than the results of Example 1. The flame retardant in Comparative Example 5 is organic phosphate, and the flame retardant performance at 3.0 mm also cannot reach the V-0 level. This shows that the compounding of halogen-free flame retardant and red phosphorus flame retardant can produce a synergistic effect, so that the obtained glass fiber reinforced nylon composite material has better flame retardant performance and better mechanical properties.

[0118] In summary, the present invention obtains a permanent antistatic halogen-free flame retardant glass fiber reinforced nylon composite material by adding components such as modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant to the system of nylon resin and glass fiber. The composite material has good mechanical properties without adding additional costs, and can also have good flame retardant properties (V-0) and excellent permanent antistatic properties (surface resistance can reach 10 9 Ω).

[0119] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A glass fiber reinforced nylon composite material, characterized in that: The raw materials for preparing the glass fiber reinforced nylon composite material include nylon resin, modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant; The halogen-free flame retardant includes an organic phosphate halogen-free flame retardant and / or a PN halogen-free flame retardant.

2. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The nylon resin includes any one of PA6, PA66, PA6I, PA612, PPA or PA46, or a combination of at least two thereof; Preferably, the content of nylon resin in the preparation raw material is 49-60 parts by weight.

3. The glass fiber reinforced nylon composite material according to claim 1 or 2, characterized in that: The modified carbon nanotubes are obtained by pre-treating carbon nanotubes; Preferably, the pretreatment comprises mixing the carbon nanotubes with a modifying agent; Preferably, the carbon nanotubes include agglomerated multi-walled carbon nanotubes and arrayed multi-walled carbon nanotubes; Preferably, the modifying agent comprises silicone oil; Preferably, the silicone oil includes any one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil or hydrogen silicone oil, or a combination of at least two thereof; Preferably, the mass ratio of the carbon nanotubes to the modifying agent is 1:(0.8-1.5); Preferably, the mixing is carried out under stirring; Preferably, the stirring speed is 60-100 r / min; Preferably, the stirring time is 2-3 min; Preferably, the content of modified carbon nanotubes in the preparation raw material is 1.5-4 parts by weight.

4. The glass fiber reinforced nylon composite material according to any one of claims 1 to 3, characterized in that: The content of the halogen-free flame retardant in the preparation raw material is 4-12 parts by weight; Preferably, the content of red phosphorus flame retardant in the preparation raw material is 3-10 parts by weight; Preferably, the mass ratio of the halogen-free flame retardant to the red phosphorus flame retardant is (5:9)-(10:4); Preferably, the organic phosphate halogen-free flame retardant includes diethyl hypophosphite halogen-free flame retardant; Preferably, the diethyl hypophosphite halogen-free flame retardant includes diethyl hypophosphite zinc and / or diethyl hypophosphite aluminum.

5. The glass fiber reinforced nylon composite material according to any one of claims 1 to 4, characterized in that: The raw materials for preparing the glass fiber reinforced nylon composite material also include glass fiber and lubricant.

6. The glass fiber reinforced nylon composite material according to claim 5, characterized in that: The length of the glass fiber is 3.0-4.5 mm; Preferably, the diameter of the glass fiber is 9-11 μm; Preferably, the content of glass fiber in the preparation raw material is 25-35 parts by weight; Preferably, the lubricant comprises any one or a combination of at least two of N,N′-bis(ethylene) stearic acid amide, stearic acid amide, paraffin wax, polyethylene wax, polypropylene wax or silicone; Preferably, the content of lubricant in the preparation raw material is 0.1-0.5 parts by weight.

7. The glass fiber reinforced nylon composite material according to any one of claims 1 to 6, characterized in that: The raw materials for preparing the glass fiber reinforced nylon composite material include the following components in parts by weight:

8. A method for preparing a glass fiber reinforced nylon composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Components including nylon resin, modified carbon nanotubes, halogen-free flame retardant and red phosphorus flame retardant are mixed, melt-extruded and granulated to obtain the glass fiber reinforced nylon composite material.

9. The method for preparing a glass fiber reinforced nylon composite material according to claim 8, characterized in that: The mixing speed is 80-120r / min; Preferably, the mixing time is 6-8 min; Preferably, the melt extrusion is carried out in a twin-screw extruder; Preferably, the temperature of each section of the twin-screw extruder is set as follows: zone 1 temperature 260-280°C, zone 2 temperature 280-300°C, zone 3 temperature 280-300°C, zone 4 temperature 280-300°C, zone 5 temperature 280-300°C, zone 6 temperature 240-260°C, zone 7 temperature 200-220°C, zone 8 temperature 190-210°C, zone 9 temperature 180-200°C, and die head temperature 250-270°C; Preferably, the residence time in the twin-screw machine is 1-2 min; Preferably, the pressure in the twin-screw extruder is 10-16 MPa.

10. Application of the glass fiber reinforced nylon composite material according to any one of claims 1 to 7 in the mining industry, automobile industry, and electronic and electrical fields.

Citation Information

Patent Citations

  • A static-resistant flame-retardant nylon composite material and its preparation method

    CN110511562B

  • A dual-antibody material and preparation method thereof

    CN114806155B